Compatibilized PC/ABS blends from solvent recycled PC and ABS polymers from electronic equipment waste. (March 2023) - Pelto, Jani; Barreto, Carlos; Anwar, Hany; Strobl, Laura; Schlummer, Martin
Abstract: This study encompasses the development of high-performance PC/ABS blends utilizing recycled PC (r-PC) and recycled ABS (r-ABS) polymers from waste electric and electronic equipment (WEEE) fractions heavily contaminated by flame retardants (FRs). Upgrading of mechanical properties was facilitated by addition of virgin ABS and additives. In total three different WEEE fractions -containing high concentrations of bromine, chloride and phosphorous were purified from polymers other than PC and decontaminated from halogenated contaminants by dissolution-precipitation CreaSolv® Process. In two studied cases the WEEE fractions were optically pre-sorted for PC before purification and decontamination. Gas chromatography (GC-ECD) and X-ray fluorescence (XRF) analyses were performed to validate efficient removal of contaminants from r-PC. The targeted mechanical properties of polymers to upgrade are notched impact strength and elastic moduli. Upgrading was achieved by using the suitable compatibilizers, and, optionally by a chain extender. First, small-scale laboratory screening test series were conducted for three compatibilizers and different ABS polymers based on micro-compounding experiments. Upscaling test series based on the pre-screening data was then organized on a conventional bench scale twin-screw extruder. SEM microstructural characterizations of the blend morphology and fractured surfaces are done to correlate structure to the mechanical properties.Dynamic mechanical analysis (DMA) and Rheological Dynamic Analysis (RDA) and Gel permeation chromatography (GPC) provided some insight to the chain branching and molecular weight distribution of r-PC, respectively. Moreover, melt rheology and solid-state mechanical properties of the compatibilized r-PC/ABS blend were thoroughly investigated. Addition of virgin ABS polymer and a suitable compatibilizer enhance the properties of the recycled PC/ABS 60/40 blends towards virgin-like, allowing easily >55% r-PC content, or in favourable cases much higher than 75% recycled polymer content when applying significant concentration of recycled ABS from CreaSolv® together with some virgin ABS. Highlights: High-performing r-PC/ABS blends were prepared using r-PC from waste electric and electronic equipment fractions. High concentrations of halogenated contaminants were effectively removed by dissolution-precipitation process (CreaSolv®). Effective strategies were explored for compatibilization of recycled polymers having initially poor properties.